2008
DOI: 10.1590/s1807-59322008000100013
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Biomechanical Comparison of Anterior Cruciate Ligament Reconstruction: Single Bundle Versus Anatomical Double Bundle Techniques

Abstract: INTRODUCTIONAnterior cruciate ligament ruptures are frequent, especially in sports. Surgical reconstruction with autologous grafts is widely employed in the international literature. Controversies remain with respect to technique variations as continuous research for improvement takes place. One of these variations is the anatomical double bundle technique, which is performed instead of the conventional single bundle technique. More recently, there has been a tendency towards positioning the two bundles throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Of those papers, 18 were selected by both observers and the remaining 4 were discussed an excluded after consensus. Therefore, 18 papers were selected for final inclusion in the systematic review [ 1 , 2 , 6 8 , 10 , 12 , 17 , 18 , 20 22 , 24 , 30 , 31 , 33 , 36 , 37 ]. The other 77 studies were mostly excluded because they did not claim that their reconstructive technique was anatomic.…”
Section: Resultsmentioning
confidence: 99%
“…Of those papers, 18 were selected by both observers and the remaining 4 were discussed an excluded after consensus. Therefore, 18 papers were selected for final inclusion in the systematic review [ 1 , 2 , 6 8 , 10 , 12 , 17 , 18 , 20 22 , 24 , 30 , 31 , 33 , 36 , 37 ]. The other 77 studies were mostly excluded because they did not claim that their reconstructive technique was anatomic.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies from these 21 studies were excluded, four22,23,39,41 because no variance and/or means were reported, one9 study that used prosthetic ligament for reconstruction, one37 study that used sheep knee specimens, one34 study that used a rectangular femoral tunnel for single bundle ACL reconstruction, two38,40 studies due to duplication of data and one35 review article. One of the included studies reported only rotational laxity 36.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the ACL appeared to be a continuous structure consisting of many different fiber bundles of different lengths and orientations. Although we did not separate the ACL stump into two or three bundles, the data generated from this study are important, as anatomic femoral tunnel placement has been a concern in single-and double-bundle ACL reconstructions [16,55], and whether a single-or double-bundle reconstruction should be performed remains controversial [1,10,26,41,43,47,49,52] and is outside the scope of this study. Finally, we do not know how much difference in placement will substantially alter the risk of either graft failure or long-term degeneration; both would require clinical confirmation.…”
Section: Discussionmentioning
confidence: 99%